Efficient Pipeline for Automating Species ID in new Camera Trap Projects - Beery, Sara; Morris, Dan; Yang, Siyu; Simon, Marcel; Norouzzadeh, Arash; Joshi, Neel (Biodiversity Information Science and Standards, 2019)
Camera traps are heat- or motion-activated cameras placed in the wild to monitor and investigate animal populations and behavior. They are used to locate threatened species, identify important habitats, monitor sites of interest, and analyze wildlife activity patterns. At present, the time required to manually review images severely limits productivity. Additionally, 70% of camera trap images are empty, due to a high rate of false triggers. Previous work has shown good results on automated species classification in camera trap data (Norouzzadeh et al. 2018), but further analysis has shown that these results do not generalize to new cameras or new geographic regions (Beery et al. 2018). Additionally, these models will fail to recognize any species they were not trained on. In theory, it is possible to re-train an existing model in order to add missing species, but in practice, this is quite difficult and requires just as much machine learning expertise as training models from scratch. Consequently, very few organizations have successfully deployed machine learning tools for accelerating camera trap image annotation. We propose a different approach to applying machine learning to camera trap projects, combining a generalizable detector with project-specific classifiers